تطوير الإرشاد الأكاديمي بجامعة السّلطان زين العابدين في ضوء التّجارب العالميّة - Muhamad Zaid, Ismail; Nashaat Abdelaziz, Abdelqader Baioumy (2017)
Academic Advising is one of the most important educational and administrative support services to the educational process of the university, as a student skips through obstacles educational career. This research aims to submit proposals for the development of Academic Advising at Universiti Sultan Zainal Abidin in the light of international experiences. The researchers used the descriptive and analytical approach, relying on studies that focused on academic guidance. Research has shown that the academic counseling at Universiti Sultan Zainal Abidin need to be developed in light of the outstanding international experiences in the field of academic guidance in terms of identifying the year mentor in all faculties of the university, and the allocation of academic advisor to students, and have a technical tasks, administrative, regulatory, and the opening of a special unit in all faculties of the university academic counseling fields include religious instruction, moral, educational, and career, psychological, and preventive, The researchers recommended that the need to take advantage of the results of this research in the development of academic advising at Universiti Sultan Zainal Abidin, and the employment of modern technology and its various applications, to facilitate communication between counselors and students.